Effect of Play Therapy on Preoperative Child Anxiety Level - Herna Alifiani (CV. Get Press Indonesia, 2024)
Children who will undergo preoperative procedures often experience significant anxiety due to uncertainty, fear of pain, and an unfamiliar hospital environment. High anxiety during the preoperative phase can affect physiological stability, complicate anesthesia, and slow postoperative recovery. Therefore, effective and easy-to-implement nonpharmacological interventions are needed to support children before surgery. This study aimed to determine the effect of play therapy on preoperative anxiety levels in children at Semen Padang Hospital.The study used a pre-experimental one-group pretest–posttest design involving 15 children aged 4–10 years scheduled for elective surgery. The intervention consisted of 20–30 minutes of play therapy using medical role-play and simple props. Anxiety levels were measured using the Modified Yale Preoperative Anxiety Scale (m-YPAS) before and after therapy. Data were analyzed with a paired t-test at a significance level p value ≤0.05. The results showed a significant decrease in anxiety after the intervention. The mean anxiety score dropped from 52.4 ± 8.7 before therapy to 32.1 ± 7.9 afterward. The paired t-test obtained a result of p = 0.001, showing a significant effect of play therapy . It shows that play therapy has a significant impact on reducing anxiety. Additionally, 80% of participants experienced a shift from moderate to low anxiety. These findings imply that nurses should integrate play therapy into standard preoperative preparation, while hospitals provide adequate facilities to ensure consistent implementation. Play therapy proves effective in reducing preoperative anxiety and can serve as an important strategy to minimize psychological stress in children before surgery.